The Characteristics of PM2.5 and O3 Synergistic Pollution in the Sichuan Basin Urban Agglomeration - Shaorong Li; Jianhui Guo; Yaqi Wang; Xinyao Lian; Jing Li (Atmosphere)
The synergistic pollution of fine particulate matter (PM2.5) and ozone (O3) has become one of the major factors affecting ambient air quality. Due to the unique geographical location of the Sichuan Basin, air pollution is more likely to occur. To assess the synergistic pollution status of PM2.5 and O3 in the Sichuan Basin, this study analyzed time series analysis, correlation analysis, and interaction analysis of PM2.5 and O3 based on hourly data from national monitoring stations in the Sichuan Basin from 2015 to 2024. Additionally, the approximate envelope method (AEM) was used to estimate the secondary PM2.5 concentration. The results showed the following: Chongqing, Zigong, Luzhou, Chengdu, and Deyang experienced severe pollution. From 2015 to 2018, these cities showed high pollution levels. Since 2019, such high levels of pollution have not been observed; during the PM2.5 pollution period (November to January of the following year), PM2.5 and O3-8h exhibited a negative correlation. During the O3-8 pollution period (May to August), PM2.5 and O3-8h showed a positive correlation; secondary PM2.5 increased with the intensity of photochemical reactions, while the concentration of primary PM2.5 showed little change compared to secondary PM2.5. Secondary PM2.5 concentrations peaked around 8:00–12:00 and reached a trough between 16:00 and 20:00 in all five cities; during the PM2.5 pollution period, the trend of O3 in the five cities was consistent. Ozone concentration showed a distinct single-peak daily variation under different PM2.5 pollution levels. As PM2.5 concentration increased, the peak O3 concentration decreased, and the valley concentration became lower. In different seasons, the increase in PM2.5 concentration can both enhance and suppress the concentration of O3. The enhanced atmospheric photochemical activity level promotes the formation of secondary components in particles. This achievement can provide a reference for the coordinated control and improvement of air quality in the Sichuan Basin.